Complex Carbocyclic Skeletons from Aryl Ketones through a Three‐Photon Cascade Reaction. Issue 14 (30th January 2020) - Næsborg, Line; Jandl, Christian; Zech, Andreas; Bach, Thorsten
Abstract: Starting from readily available 7‐substituted 1‐indanones, products with a tetracyclo[5.3.1.0 1, 7 0 4, 11 ]undec‐2‐ene skeleton were obtained upon irradiation at λ =350 nm (eight examples, 49–67 % yield). The assembly of the structurally complex carbon framework proceeds in a three‐photon process comprising an ortho photocycloaddition, a disrotatory [4π] photocyclization, and a di‐π‐methane rearrangement. The flat aromatic core of the starting material is converted into a functionalized polycyclic hydrocarbon with exit vectors in three dimensions. Ring opening reactions at the central cyclopropane ring were explored, which enable the preparation of tricyclo[5.3.1.0 4, 11 ]undec‐2‐enes and of tricyclo[6.2.1.0 1, 5 ]undecanes. Abstract : Running up that hill : A major bond reorganization takes the marked arene carbon atom from "flatland" to the summit of three‐dimensional hydrocarbon hills. Three photons initiate a cascade reaction to convert the flat aromatic cores of the starting materials into functionalized pentacyclic hydrocarbons (11 examples, 37–67 %) that are prone to further ring opening in situ or through a two‐step process.